Implementasi Beracara Secara Prodeo di Pengadilan Negeri Meulaboh - Trisna, Nila; Kahar, Ulya Masyita (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Court fee waiver services (Prodeo) for the underprivileged, as stipulated in the Supreme Court Regulation of the Republic of Indonesia No. 01 of 2014, is that any person or group of people who cannot afford it economically can do a case for free. At the Meulaboh District Court, prodeo cases did not work as they should, so the public did not know that free litigation services were available. This study aims to find out how the Prodeo trial procedure is, as well as the factors that cause the loss of Prodeo at the Meulaboh District Court. This study uses an empirical juridica method, to find out how efficiently the law works in society, government and legal entities. The use of Prodeo is only for underprivileged people by fulfilling the conditions that have been set and being able to follow all procedures in dealing with prodeo. The factor that causes the loss of Prodeo is due to the lack of isocialization specifically both directly and online media, this is what causes the public to not know about Prodeo cases and causes the loss of the Prodeo budget. keywords: Law, Prodeo, justice.